Psychosocial effects of tinnitus on the elderly individuals with normal hearing abilities in Ibadan, Oyo State Nigeria (2013)
The study sampled 130 elderly listeners comprising 68 males and 72 females, aged between 65 and 74 years and resident in both urban and rural areas of Ibadan metropolis as the participants for the study under a descriptive research design of the ex post facto type. A standardized Tinnitus Research Questionnaire (TRQ) consisting of twenty items with a reliability coefficient of 0.90 was the instrument used for data collection to answer the three research questions and four hypotheses. The data collected based on the research questions were analysed with the use of mean and chi- square, while Pearson's chi- squared test and Independent t- test were used to test the null hypotheses at 0.05 level of significance. It was discovered that due to tinnitus, majority of the participants experienced concentration difficulty and despair. Majority of them also felt frustrated and manifested some kinds of abnormal behaviour due to tinnitus. However, there was no significant difference between psycho- social reactions of elderly listeners sampled in rural and urban areas. Based on these findings, it was recommended that elderly individuals should avoid exposure to noise, emotional stress, worry and unprescribed drugs; and should be encouraged to go for audiological tests at regular intervals.